Reproductive wastage rate of crossbred dairy bulls with reference to level of exotic inheritance and number of breed components - TYAGI, S; MANDAL, D K; KUMAR, MAHESH; MATHUR, A K (The Indian Journal of Animal Reproduction, 2023)
Studies conducted on crossbred bulls to observe the impact of various levels of Holstein-Friesian inheritance and numbers of indigenous breeds components (Sahiwal, Red Sindhi, Tharparkar, Hariana) on the reproductive wastage rate of bulls, used in artificial insemination programme revealed that on over all basis, 8.36% bulls were culled due to non-donation of semen in artificial vagina, and only 41.11 % bulls ( out of those donated semen) produced freezable quality semen. As the number of indigenous breeds component increased, the number of crossbred bulls producing freezable quality semen decreased. Similarly, with the increase in exotic inheritance beyond 62.5%, the proportion of crossbred bulls producing freezable quality semen also decreased.